PENGARUH PERENCANAAN OPERASI PENANGGANAN DARURAT BENCANA TERHADAP EFEKTIVITAS KERJA KASI KEDARURATAN DAN LOGISTIK BPBD SUMEDANG - Fathoni, Abdurrahmat; Sulaeman, Asep; Kusmayadi, Dedi (JRPA - Journal of Regional Public Administration, 2020)
The purpose of this study is to find out the Effect of Disaster Emergency Management Operations on The Effectiveness of Work on Emergency and Logistics in the Sumedang District Disaster Management Agency. The research method used in this research is a quantitative research method with two methods of data collection, namely literature studies and field studies that include observation, questionnaire, interview and documentation. For the spread of angket carried out to all employees of ASN (State Civil Apparatus) and Non-ASN (Pusdalops or Disaster Management Operations Control Center) in the Sumedang Regional Disaster Management Agency which amounted to 40 people. Based on the results of research it is known that disaster emergency management operations planning in emergency and logistics at the Sumedang Regional Disaster Management Agency is 88.4%. Furthermore, the Effectiveness of Work on Emergency and Logistics in the Sumedang District Disaster Management Agency is 90.5%. Based on correlation tests it is known that there is a very strong relationship between Disaster Emergency Management Operation Planning and Work Effectiveness in Emergency and Logistics Kasi at the Sumedang District Disaster Management Agency with a correlation coefficient of 0.808. The Effect of Disaster Emergency Management Operations Planning on The Effectiveness of Work on Emergency and Logistics Kasi in the Sumedang District Disaster Management Agency based on determination tests is in a strong category with a coefficient of determination of 0.653 or if percentageed by 65.3%. The remaining 34.7% was affected by other factors not studied in the study.